2017
DOI: 10.1097/meg.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thiopurine S-methyltransferase gene polymorphisms in patients with inflammatory bowel disease from the island of Crete, Greece

Abstract: This study showed a lower frequency of total TPMT variants and a higher frequency of TPMT*3B in Cretan IBD patients compared with other Caucasian populations. The presence of the G460A mutation is associated with the development of leukopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
“…A cohort study including Greek IBD patients showed that the presence of the single nucleotide polymorphism (SNP) TPMT 460A > G (accounting for both TPMT variants *3A and *3B) was associated with a significant higher risk for thiopurine induced early (within 8 weeks) or late (after 8 weeks) neutropenia, but TPMT 719A > G (accounting for the TPMT *3C variant) was not . In an Asian population a specificity of 100% (163/163) but a sensitivity of 6% (2/36) for early TIL was demonstrated with regard to TPMT *3C, from which they concluded that testing for TPMT variants has a limited predictive value for leukopenia in the Asian population .…”
Section: Resultsmentioning
confidence: 99%